2016
DOI: 10.1002/bjs.10146
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review of antibiotic treatment for acute calculous cholecystitis

Abstract: Antibiotics are not indicated for the conservative management of ACC or in patients scheduled for cholecystectomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
0
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(31 citation statements)
references
References 83 publications
0
28
0
3
Order By: Relevance
“…The use of preoperative prophylactic antibiotics is not suitable for low-risk patients undergoing LC. The main purpose of starting antibiotics in surgically managed cases of ACC is to prevent perioperative infectious complications[46], however, according to van Dijk et al[47] in recent systematic review, which assessed its effect in the course of ACC conclude: They are not effective for patients undergone to non-operative treatment neither in those one selected for cholecystectomy.…”
Section: Antimicrobial Treatmentmentioning
confidence: 99%
“…The use of preoperative prophylactic antibiotics is not suitable for low-risk patients undergoing LC. The main purpose of starting antibiotics in surgically managed cases of ACC is to prevent perioperative infectious complications[46], however, according to van Dijk et al[47] in recent systematic review, which assessed its effect in the course of ACC conclude: They are not effective for patients undergone to non-operative treatment neither in those one selected for cholecystectomy.…”
Section: Antimicrobial Treatmentmentioning
confidence: 99%
“…Similarly, the use of antibiotics is disputable even in the conservative management of acute cholecystitis. A recent systematic review 16 demonstrated that there is little evidence on this subject, and the available evidence is of poor quality and has a high risk of bias. The review identified only one small study 17 that compared antibiotic treatment with a conservative strategy without antibiotics, showing that antibiotics did not improve the outcome of acute calculous cholecystitis.…”
Section: Discussionmentioning
confidence: 99%
“…6 In contrast, a recent metaanalysis showed that antibiotics are not indicated in the conservative management of most patients with AC or in those scheduled for cholecystectomy, and should only be used in patients with moderate or severe AC. 18 In our study, most patients with histopathological AC (88%) were treated with antibiotics. However, 66% of patients with no histopathological evidence of AC were also treated with antibiotics raising the possibility that they may have been overtreated.…”
Section: Discussionmentioning
confidence: 62%